First report of Bipolaris secalis causing leaf spot disease on Brachiaria (syn. Urochloa) grass - Uzayisenga, Bellancile; Mutimura, M.; Muthomi, J.W.; Mwang’ombe, A.W.; Ghimire, Sita R. (Wiley, 2023)
Brachiaria (syn. Urochloa) grass is rapidly gaining popularity as a new forage option in sub-Saharan Africa including Rwanda. During disease surveillance in Rwanda in 2018–2019, Brachiaria foliage was found with necrotic purple spots with a whitish centre on the upper surface of leaves (Figure 1). Diseased leaves were collected from farmers' fields in Bugesera (02°08'33.4'' S, 030°09'08.8'' E), Huye (02°28'54.8˝ S, 29°46'.56.9˝ E), Nyagatare (01°18'56.16˝ S, 030°18'18.24˝ E) and Rwamagana (01°58'49.62˝ S, 030°27'29.82˝ E) districts. Pathogen isolation and identification was done in the Plant Pathology Laboratory of the Rwanda Agriculture and Animal Resources Development Board in Rubona, Rwanda. The pathogen was isolated and grown on commercial potato dextrose agar (PDA) amended with ampicillin (100 μg ml−1) and incubated at 24°C for two weeks (Ghimire et al., 2011).